Development of Plant Maintenance Management System (PMMS): a Case Study - N.A., Che Azhar; M.A., Mansor (2013)
In large plant industry, it is not easy to maintain the machine performance without using any method such as checklist system. Manual checklist is one of common maintenance checklist used in industry. All machine, equipment and part of machine that needs to be check will be written down for the employee to do maintenance checks. Convert manual checklist to the Plant Maintenance Management System (PMMS) can improve the way of employees work and make employer easy to manage the plant. Therefore, a new system was design to maintain the equipment so that the activities are more efficient and cost effective. The system consists of three frames that connect to each other. The frames divide to section, equipment and checklist. This system also builds to prevent data from arbitrarily changed. Only certain officers or staffs allowed making modifications to data. This system developed for convenience of staff and officers in carrying out their duties. Using this system, a company can make the office environment a paperless environment.